PENERAPAN TEKNIK ICE BREAKING DALAM MENINGKATKAN MINAT BELAJAR MATEMATIKA MAHASISWA - Kadek Suryati; Evi Dwi Krisna (Widyadari, 2024)
The purpose of this study is to determine students' interest in learning mathematics in a mathematics course. This type of research is descriptive qualitative. The sample for this study consists of second-semester students majoring in computer engineering systems at the Institute of Business and Technology Indonesia (INSTIKI) Campus. The research activity design includes three stages: the preparation stage, the field implementation stage, and the post-field stage. In the preparation stage, the following activities were conducted: creating a research design, conducting preliminary observations, selecting and determining the class, and preparing research instruments. The data sources for this research were obtained from questionnaires, interviews, observations, and documentation carried out in the selected class. The data collection techniques used by the researcher include student response questionnaires, observations, interviews, and documentation. The questionnaire used in this study is a closed/structured questionnaire about students' interest in learning mathematics. Data analysis was conducted descriptively based on the data collected from the instruments used. The results of the study showed that students' interest in terms of enjoyment in attending mathematics courses using ice-breaking techniques was 94%, interest in students' attention focus on mathematics courses using ice-breaking techniques was 85%, interest in student engagement in learning activities using ice-breaking techniques was 95%, and interest in students' attraction to participating in learning with ice-breaking techniques was 84%.